2014
DOI: 10.1126/science.1249361
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Protein Kinase RIPK3 Determines Whether Cells Die by Necroptosis or Apoptosis

Abstract: Receptor-interacting protein kinase 1 (RIPK1) and RIPK3 trigger pro-inflammatory cell death termed "necroptosis." Studies with RIPK3-deficient mice or the RIPK1 inhibitor necrostatin-1 suggest that necroptosis exacerbates pathology in many disease models. We engineered mice expressing catalytically inactive RIPK3 D161N or RIPK1 D138N to determine the need for the active kinase in the whole animal. Unexpectedly, RIPK3 D161N promoted lethal RIPK1- and caspase-8-dependent apoptosis. In contrast, mice expressing R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
554
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 563 publications
(593 citation statements)
references
References 25 publications
24
554
2
1
Order By: Relevance
“…Consistent with our data, that study demonstrated that RIPK3 catalytic activity is dispensable for apoptosis, but essential for necroptosis. However, in contrast to that study, 42 we observed that apoptosis could proceed, to some extent, in the absence of RIPK1.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with our data, that study demonstrated that RIPK3 catalytic activity is dispensable for apoptosis, but essential for necroptosis. However, in contrast to that study, 42 we observed that apoptosis could proceed, to some extent, in the absence of RIPK1.…”
Section: Discussioncontrasting
confidence: 99%
“…78,79 Although RIP3-driven necroptosis contributes to the perinatal defects associated with RIP1 deficiency, it is not the sole underlying mechanism. 63 This is supported by recent studies demonstrating an important role for RIP1 in protecting against TNF-and caspase 8-driven apoptosis. 76,79 Under conditions of TNF stimulation, or during virus infection, that trigger RIP1-dependent necrosis, RIP3 promotes necrosis-specific phosphorylation of RIP1, thus forming a pro-necrotic necrosome complex.…”
Section: Rip1 and Rip3 As Drivers Of Necroptosismentioning
confidence: 65%
“…75 This may, at least partly, underlie the perinatal lethality associated with RIP1 deficiency but would require that any such protective effects of RIP1 are independent of kinase activity as RIP1 kinase dead knockin mice survive to adulthood. 63,76,77 In addition, during development the physiological role of RIP1 in regulating RIP3-driven necroptosis appears to be highly dependent on the stage of development with RIP1 being required for TNF-induced necroptosis at E10.5 78 but inhibiting necroptosis and associated inflammation at later stages of development. 78,79 Although RIP3-driven necroptosis contributes to the perinatal defects associated with RIP1 deficiency, it is not the sole underlying mechanism.…”
Section: Rip1 and Rip3 As Drivers Of Necroptosismentioning
confidence: 99%
“…103,104 In contrast, it is very puzzling that inhibition and gene deletion of RIPK1 and RIPK3 result in different phenotypes. Inhibition of RIPK3 kinase activity activates caspases and tissue injury, 97 whereas deletion of Ripk3 does not cause any abnormality. 105 Conversely, inhibition of RIPK1 by knocking-in a kinase-dead version of RIPK1 or necrostatin-1 treatment does not cause any tissue injury, 47,97 whereas deletion of Ripk1 causes cell death and systemic inflammation in vivo.…”
Section: Tak1mentioning
confidence: 99%
“…Inhibition of RIPK3 kinase activity activates caspases and tissue injury, 97 whereas deletion of Ripk3 does not cause any abnormality. 105 Conversely, inhibition of RIPK1 by knocking-in a kinase-dead version of RIPK1 or necrostatin-1 treatment does not cause any tissue injury, 47,97 whereas deletion of Ripk1 causes cell death and systemic inflammation in vivo. 80,81 It should be of immediate interest to elucidate the molecular mechanism of how TAK1, RIPK1 and RIPK3 interplay to inhibit apoptosis pathways.…”
Section: Tak1mentioning
confidence: 99%